2017
DOI: 10.3390/metabo7020029
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy for Detection of 2-Hydroxyglutarate as a Biomarker for IDH Mutation in Gliomas

Abstract: Mutations in the isocitrate dehydrogenase (IDH)1/2 genes are highly prevalent in gliomas and have been suggested to play an important role in the development and progression of the disease. Tumours harbouring these mutations exhibit a significant alteration in their metabolism resulting in the aberrant accumulation of the oncometabolite 2-hydroxygluarate (2-HG). As well as being suggested to play an important role in tumour progression, 2-HG may serve as a surrogate indicator of IDH status through non-invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 66 publications
0
34
1
Order By: Relevance
“…MRS uses the proton signals to determine relative concentrations of target metabolites rather than an anatomical image. In various studies, MRS has been shown capable of identifying regions of tissue enriched with stem-like cell-enriched foci [131], detecting tumours with mutations in the isocitrate dehydrogenase (IDH) genes [132,133], and assessing response to various therapies such as radiation and PI3K/mTOR inhibitors [134,135]. Further, the use of hyperpolarized (HP) contrast agents can significantly increase the sensitivity of MRS by enhancing the signal-to-noise ratio [136,137].…”
Section: Medical Imaging and Histopathologymentioning
confidence: 99%
“…MRS uses the proton signals to determine relative concentrations of target metabolites rather than an anatomical image. In various studies, MRS has been shown capable of identifying regions of tissue enriched with stem-like cell-enriched foci [131], detecting tumours with mutations in the isocitrate dehydrogenase (IDH) genes [132,133], and assessing response to various therapies such as radiation and PI3K/mTOR inhibitors [134,135]. Further, the use of hyperpolarized (HP) contrast agents can significantly increase the sensitivity of MRS by enhancing the signal-to-noise ratio [136,137].…”
Section: Medical Imaging and Histopathologymentioning
confidence: 99%
“…In hypoxic environments where glucose metabolism is diverted to anaerobic lactate production, mutations in mitochondrial IDH2 provide a continued source of citrate for lipid synthesis, by allowing reductive carboxylation of glutamine‐derived α‐KG . The oncometabolite 2‐hydroxyglutarate is produced by many cancer‐specific IDH1 and IDH2 mutations, and has widespread epigenetic effectors by altering DNA methylation …”
Section: Tumor Progression and Regressionmentioning
confidence: 99%
“…The picture is further complicated because ChoK is not the only enzyme that contributes to PC accumulation; it can be produced directly by the actions of PLC on PtdCho, or by the hydrolysis of GPC as a source of additional choline for subsequent phosphorylation. Recent MRS applications have been used to detect changes in choline metabolism due to IDH mutations in glioma, explore the role of the glycerophosphodiesterase genes GDPD5 and GDPD6 on breast cancer cell migration/invasion, and profile metabolic changes in response to HIF1 and HIF2 suppression …”
Section: Imaging Metabolic Lipid Changesmentioning
confidence: 99%
“…Despite the pervading observations that the IDH mutation not only causes an increase in 2HG but also a change in several other metabolites, either at the initial diagnosis (Figure ) or during assessment of response to treatment (Figure ), the change in the metabolomic pattern seems not to be regarded with much interest in the literature. This seems surprising because 2HG is a non‐invasive diagnosis and prognosis biomarker for IDH mutation, and it is druggable . Perhaps small cohort sizes collected by each individual study and the difficulty of integrating these data with other studies using different acquisition and processing parameters may provide an explanation for this low uptake by clinical centres.…”
Section: Mrs(i)‐detectable Metabolic Hallmarks Of Cancer: Applicationmentioning
confidence: 99%